2014
DOI: 10.1371/journal.pone.0105455
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Mountain Pine Beetle Symbiont Leptographium longiclavatum and the Implication on the Multipartite Beetle-Fungi Relationships

Abstract: Over 18 million ha of forests have been destroyed in the past decade in Canada by the mountain pine beetle (MPB) and its fungal symbionts. Understanding their population dynamics is critical to improving modeling of beetle epidemics and providing potential clues to predict population expansion. Leptographium longiclavatum and Grosmannia clavigera are fungal symbionts of MPB that aid the beetle to colonize and kill their pine hosts. We investigated the genetic structure and demographic expansion of L. longiclav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 87 publications
(144 reference statements)
3
19
0
Order By: Relevance
“…with what has been reported in population genetic analyses with much broader sampling across western North America (Tsui et al 2012(Tsui et al , 2014Ojeda Alayon et al 2017). The differences in genetic variability among species could be explained by mutation rate, population history, or mode of reproduction.…”
Section: O Montiumsupporting
confidence: 75%
See 3 more Smart Citations
“…with what has been reported in population genetic analyses with much broader sampling across western North America (Tsui et al 2012(Tsui et al , 2014Ojeda Alayon et al 2017). The differences in genetic variability among species could be explained by mutation rate, population history, or mode of reproduction.…”
Section: O Montiumsupporting
confidence: 75%
“…Both mating type loci were found in these fungi and the alleles were in equilibrium overall and in most populations tested (DiGuistini et al 2011;Tsui et al 2013). Sexual reproduction is also supported by the large number of MLGs that we consistently observed in these fungi (this paper; Tsui et al 2012Tsui et al , 2014. One explanation for the lack of relatedness among these fungi is that they could be vectored by unrelated beetles.…”
Section: O Montiumsupporting
confidence: 61%
See 2 more Smart Citations
“…has thus improved our knowledge of these organisms in their natural environments. A few well-documented epidemics caused by introduced pathogens have allowed the reconstruction of the invasion pathways or the exclusion of potential sources by testing different scenarii of introduction, using recent advances in molecular and statistical Bayesian analysis (Grünwald and Goss 2011;Barrès et al 2012;Graça et al 2013;Tsui et al 2014). For instance, molecular studies completed since the European invasion of Hymenoscyphus fraxineus strongly suggested that the fungus originates from East Asia, (Gross et al 2014), where no epidemics have been reported on the local ash species.…”
mentioning
confidence: 99%